2009
DOI: 10.1386/pjss.8.2.133/1
|View full text |Cite
|
Sign up to set email alerts
|

A first approach to perceptions of social norms regarding reactions towards innocent and non-innocent victims

Abstract: This article aims to study whether individuals perceive secondary victimisation reactions as counter-normative or normative (at both a prescriptive and descriptive level) and whether these judgments depend on the victim's innocence (responsibility), the participants' belief in a just world and the sex of the victim. An experimental study was conducted and, overall, most ratings were in the direction of non-secondary victimisation reactions, independently of the innocence of the victim and of the norm consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…As far as we know, the studies presented in this paper are the first attempt to investigate the perception of prescriptive norms regarding reactions to victims of bullying. A study conducted by Alves (2005; Alves & Correia, in press) about the perception of norms regarding reactions to victims may provide some hints on the issue. In Alves and Correia (in press) study, participants read the case of either an innocent (a sober and cautious driver who was hit by a drunk driver) or a non‐innocent victim (a drunk driver that hit a sober and cautious driver) who suffered severely (85% of the body burnt, disfigurement, no eye‐lids, need of constant eye lubrication) and permanently (need of permanent medical care, with the victim’s life expectation being equivalent to the average population according to doctors).…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, the studies presented in this paper are the first attempt to investigate the perception of prescriptive norms regarding reactions to victims of bullying. A study conducted by Alves (2005; Alves & Correia, in press) about the perception of norms regarding reactions to victims may provide some hints on the issue. In Alves and Correia (in press) study, participants read the case of either an innocent (a sober and cautious driver who was hit by a drunk driver) or a non‐innocent victim (a drunk driver that hit a sober and cautious driver) who suffered severely (85% of the body burnt, disfigurement, no eye‐lids, need of constant eye lubrication) and permanently (need of permanent medical care, with the victim’s life expectation being equivalent to the average population according to doctors).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals engage in positive self-other distinction, as our results show, by indicating that they themselves adopt those norms to an even higher extent than most other people. Given the strong influence of norms on behaviors (Nolan et al, 2008) and that injunctive norms protect victims (Alves & Correia, 2009) to inform individuals about this counterintuitive discrepancy which they are most probably unaware of. As in other domains, these campaigns may not prevent automatic reactions from happening.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that social norms can powerfully influence people's behaviors (Shultz, Nolan, Cialdini, Goldstein, & Griskevicius, 2007), even though individuals may fail to notice such influence (Nolan, Shultz, Cialdini, Goldstein, & Griskevicius, 2008). To our knowledge, however, only Alves and Correia (2009) have directly applied social norms, specifically the conceptual distinction between injunctive and descriptive social norms, to the study of various secondary victimization and non secondary victimization reactions towards innocent and noninnocent victims (but see Simons & Piliavin, 1972;Snyder, Kleck, Strenta, & Mentzer, 1980, for indirect evidence on derogation and avoidance, respectively).…”
Section: Social Norms and The (Counter-) Normativity Of Reactions Towmentioning
confidence: 99%
See 1 more Smart Citation
“…In most victim blame studies, researchers assess explicit blame, with items such as “To what extent do you think that [victim’s name]’s behavior is to blame for [victim’s condition]?” (e.g., [8,9]). One problem with these measures is that recent findings from several countries [10–13] show that blaming victims for their fate is often counternormative. Thus, people might not explicitly report blame [14].…”
Section: Introductionmentioning
confidence: 99%